Nurturing a Sustainable Harvest Pivoting on Green HRM in Agricultural Productivity and The Environment - Munajim, Ahmad; Vidiati, Cory; Selasi, Dini; Nauroh, Izzwah; Arie Pratama, Fidya (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This paper shows the performance of HR collaboration on the environment, in other words, GHRM can increase agricultural productivity while protecting the environment. The method is qualitative with a case study on a farm in Cirebon Regency, West Java, which applies the concept of GHRM. Data were collected through interviews, observations, and document analysis through SWOT Analysis. The findings of GHRM can be achieved through fostering a workforce that cares about the environment, encouraging innovation and collaboration, influencing organisational culture and decision-making, and generating new businesses such as garden/nature tourism, educational tourism, and spiritual tourism. The novelty of the research from the SWOT analysis is that collaborative GHRM leads to new sustainable businesses. Limitations The study was only conducted in Cirebon Regency, West Java—implications of the research directly on stakeholders and government through policies that favour collaboration for sustainable business.